Retrospective Study of Factors Affecting Efficacy of Therapy with Dye Pulsed Light for Erythematotelangiectatic Rosacea - Leran Zhao; Cong You; Han Chen; Jiangyi Wang; Junya Cao; Manli Qi; Shuping Hou; Xin Zheng; Lili Shao; Quanzhong Liu (Adis, Springer Healthcare, 2020)
Abstract Introduction Dye pulsed light (DPL) was proven to be effective at treating erythematous and telangiectatic skin disorders. However, there are limited data on the efficacy of DPL treatment for erythematotelangiectatic rosacea (ETR), and researchers do not fully understand the factors that may affect the efficacy. Here, we performed a study to investigate the efficacy of DPL treatment for ETR and determine the factors affecting that efficacy. Methods Sixty-five patients with ETR underwent three treatment sessions with DPL at 4-week intervals and were followed up at 4 weeks after the last treatment session. Skin type, sex, age, lesion site, severity of erythema and telangiectasia, VISIA percentile ranking, clinical photographs and red area images were recorded at baseline. The post-treatment erythematous and telangiectatic scores and VISIA percentile rankings were recorded, and the effects of different personal and clinical factors on the efficacy were statistically analysed. Results The erythema and telangiectasia scores and VISIA percentile rankings showed significant improvement after the DPL procedures (p < 0.01). With regard to erythema, treatment efficacy was not affected by any of the investigated variables, including pre-treatment erythema scores, skin type, pre-treatment VISIA percentile ranking, sex, age and lesion site (p > 0.05). With regard to telangiectasia, the treatment efficacy was greater for mild telangiectasia than for severe telangiectasia (odds ratio = 4.14, p < 0.05). There was no significant difference in treatment efficacy between the moderate and severe categories (odds ratio = 4.00, p > 0.05). Conclusion DPL is not the optimal procedure for treating severe telangiectasia in patients with ETR, whereas the efficacy of the treatment for erythema was not affected by the severity of the condition.